2019
DOI: 10.16965/ijar.2019.298
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis and Sexual Dimorphism of Hyoid Bone in Telangana Population

Abstract: Determination of sex is of crucial importance in forensic investigations, when only a part of the body or skeletal remains are available. The present study focussed on the sexual dimorphism of hyoid bone in Telangana population by using morphometric analysis.Materials and methods: The present study was carried out on a total of 60 hyoid bones in which 30 were of male and 30 were of female individuals. The bones were obtained from the department of Anatomy, Osmania Medical College and Deccan College of Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hyoid bone morphometry is one of the tools that anatomists and anthropologists use to identify sex (Okasi et al, 2018;Vohra & Kulkarni, 2017). Sexual dimorphism in size and shape have been reported (Fakhry et al, 2013;Urbanova et al, 2013), with a number of studies confirming that the dimensions of the male hyoid bone are larger in males than females, but such findings are based on postpubertal hyoid bone measurements (Okasi et al, 2018;Sameera & Rao, 2019;Urbanova et al, 2013). Overall, our findings are generally consistent with sex-specific differences reported that include the following dimensions: wider distance between the two greater cornua with males having greater width (Urbanova et al, 2013); wider hyoid body in males (distance between the left and right central points of junction of the greater cornu and the hyoid body) (Okasi et al, 2018;Vohra & Kulkarni, 2017); greater length of the greater cornu in males (Vohra & Kulkarni, 2017), specifically the left greater cornu (Okasi et al, 2018); and the common Vshaped hyoid angle in females (Urbanova et al, 2013), formed by the intersection of lines extending between the two greater cornu, despite inconsistencies in findings on significance (Ichijo et al, 2016;Okasi et al, 2018).…”
Section: Sexual Dimorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyoid bone morphometry is one of the tools that anatomists and anthropologists use to identify sex (Okasi et al, 2018;Vohra & Kulkarni, 2017). Sexual dimorphism in size and shape have been reported (Fakhry et al, 2013;Urbanova et al, 2013), with a number of studies confirming that the dimensions of the male hyoid bone are larger in males than females, but such findings are based on postpubertal hyoid bone measurements (Okasi et al, 2018;Sameera & Rao, 2019;Urbanova et al, 2013). Overall, our findings are generally consistent with sex-specific differences reported that include the following dimensions: wider distance between the two greater cornua with males having greater width (Urbanova et al, 2013); wider hyoid body in males (distance between the left and right central points of junction of the greater cornu and the hyoid body) (Okasi et al, 2018;Vohra & Kulkarni, 2017); greater length of the greater cornu in males (Vohra & Kulkarni, 2017), specifically the left greater cornu (Okasi et al, 2018); and the common Vshaped hyoid angle in females (Urbanova et al, 2013), formed by the intersection of lines extending between the two greater cornu, despite inconsistencies in findings on significance (Ichijo et al, 2016;Okasi et al, 2018).…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Though hyoid bone fusion is typically absent prior to age 20, it does not occur in everyone during older adulthood, for unknown reasons (Fisher et al, 2016; Ichijo et al, 2016). While the sex‐specific timing of hyoid bone fusion and hyoid bone density has been explored across the lifespan (e.g., Fisher et al, 2016), knowledge on the three‐dimensional (3D) growth of the hyoid body and its greater cornua, particularly during early childhood, is scant (Harun et al, 2007; Sameera & Rao, 2019; Sheng et al, 2009; Vohra & Kulkarni, 2017). Also, although the hyoid bone responds to surgical intervention of mandibular deformities by adapting to the mandible's new placement (Kamano, Terajima, Kitahara, & Takahashi, 2017), given its functional relationship to the mandible as mediated by their attachments to the tongue, knowledge on how the position of the hyoid bone relative to the mandible changes across typical development is limited (Ichijo et al, 2016; Mitani & Sato, 1992; Okasi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%